Female Political Power and the Complexity of Social Barriers in Pakistan - Umer Khayyam; Fariha Tahir (NUST Journal of Social Sciences and Humanities, 2021)
Women constitute half of the world’s population; however, they are seldom represented according to their numbers. This underrepresentation is prevalent in all socio-economic aspects and in societies across the world. Irrespective of geographical location, women continue to be discriminated, especially in the political domain. This paper has deployed quantitative techniques, based on secondary data of independent sources. It is to check the actual level of female political participation in Pakistan, since independence. The level of female political participation in Pakistan union-council to upper-house (Senate) is studied in comparison with other nations in Asia and the world. It is even at the eve of Pakistan’s 70th anniversary, women are restricted to education and health sectors only, whereas, in the political arena societal factors, cultural taboos, and religious misinterpretation are found to be the main hurdles. Also, the persistent patriarchal mindset in the social system remains the underlying belief for low levels of female political participation.